Peranan Kode Etik Jaksa Pada Pengawasan dan Pertanggungjawaban Dalam Menjaga Integritas Penegakan Hukum di Indonesia - Putri, Nasywa Awalia; Lewoleba, Kayus Kayowuan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the role of the prosecutor's code of ethics in supervision and accountability to maintain the integrity of law enforcement in Indonesia, considering that integrity is the main foundation of public trust in the justice system. The purpose of this study is to analyze the extent to which the prosecutor's code of ethics acts as an instrument for controlling professional behavior and the effectiveness of the mechanism for supervision and accountability for ethical violations in the prosecutor's office. This study uses a normative legal research method with a statute approach and a conceptual approach, as well as data collection techniques through literature studies. The results of the study indicate that although the prosecutor's code of ethics has been regulated normatively and becomes a guideline for professional behavior, its implementation still faces challenges, such as weak internal supervision, less strict sanctions, and limited external supervision authority by the Prosecutor's Commission. Various cases of violations of the code of ethics, such as abuse of authority and conflicts of interest, indicate a gap between rules and practices. Therefore, it is necessary to strengthen the supervision system, update the substance of the code of ethics, and increase transparency and accountability to realize law enforcement with integrity and public trust.